'In the kitchen and around the table': on the way towards commensal (mutually beneficial) relationships – a project encouraging autonomy in young people with learning disabilities. Issue 1 (2nd January 2018) - Greco, Alba
ABSTRACT: Valerie Sinason writesOpening your eyes … to the realisation that you will not be an Austen, Einstein, Madonna or Picasso can be painful enough to the ordinary adolescent. Opening your eyes to admitting you look, sound, walk, talk, move or think differently from the ordinary, average person … takes greater reserves of courage, honesty and toleration of one's envy. (Sinason, 1992, p. 20) This paper addresses the painful difference between ordinary adolescents and those with learning disabilities, and describes a task which might demand even greater reserves of courage from a group of youth tutors and other specialists in charge of supporting 13 adolescents and young adults with mild learning disabilities towards some degree of autonomy where each young person was to be helped to live autonomously in an apartment of their own and to manage their own daily life. One was Alberto, a young man who sat pretending to read a newspaper, but was, in fact, functionally illiterate. Two others, Gianna and Mario, played the role of 'fiancés', but needed much help if they were to access a real intimate relationship. A monthly work discussion seminar was an invaluable tool which helped to contain the anxieties, fears and painful feelings of helplessness experienced by the professionals involved. The process of contributing to a work discussion group helped them to keep alive their faith in the growth of the mind and to experience the surprise of 'unexpected gains'.